Pengaruh Penerapan Model Inquiry Learning Berbantuan Modul Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VII SMPN 12 Padang - Darmansyah, Darmansyah; Zelhendri, Zelhendri; Pratiwi, Rahmi; Hidayatulah, Serlin (Indo-MathEdu Intellectuals Journal, 2024)
Based on the results of observations at SMPN 12 Padang, a problem was found that most of the grade VII students in the Social Sciences (IPS) subject still did not reach the limit of the Learning Goal Achievement Criteria (KKTP) that had been set. This is because the teaching and learning process is still centered on teachers (teacher centred) and the use of models that are not suitable for learning activities. This study proves that the application of the Inquiry Learning learning model supported by learning modules significantly improves student learning outcomes in social studies subjects in grade VII of SMPN 12 Padang. This study uses a quasi-experimental method with a pretest-posttest control group design. The research sample was taken by purposive sampling by dividing students into two groups: an experimental group taught using the Inquiry Learning model and a control group taught by conventional methods. The main data collection technique is through learning outcome tests given before and after treatment. Data analysis was carried out using a t-test to compare the average post-test scores of the two groups. The results of the analysis showed a significant difference between the two groups, where the experimental group obtained a higher average score. This indicates that the Inquiry Learning model is effective in improving students' conceptual understanding of social studies subjects.